Detection of Vital Anatomical Landmarks in Lower Posterior Premolars and First Molar Area (BuccallyPositioned)During Different Surgical Intervention Using Cone Beam Ct Scan - Hakiem Tawfieq , Ali (Diyala Journal of Medicine, 2023)
Background: The mental foramen (MF) is a very important structure; to avoid any trauma to mental nerve may be occur and in order to avoid that, its position, variation in anatomy and shapes should be clearly determined before any surgical procedure. Objective: To detect the exact position of MF and thickness of cortical plates in lower premolars and first molars among the Iraqi resident. Patients and Methods: For this prospective study, a total of 92 Iraqi adults patients (51 females, 41 males; age range 18-69 years). From October 2020 to February 2021, patients aged range from 25 to 65 years old.Five types of classification we used: Type 1, MF under the root of the lower first premolar. Type 2, MF between the root of mandibular first & second premolar. Type 3, MF below the root of the mandibular second premolar. Type 4, MF between the root of lower second premolar & first molar. Type 5, MF below the root of the lower first molar. Bone thickness is measured in the horizontal direction on the both side lingually and buccally. Results: The most common situation of the MF was below the root of lower second premolar. Conclusion: Significant difference can be noted in the mean of the distance between MF and root apex in both gender, also significant difference in mean of bone thickness noted between both genders on both sides.